Spanish clitic clusters - Cuervo, María Cristina (Borealis – An International Journal of Hispanic Linguistics, 2013)
This paper deals with a small set of data from clusters of three clitics in Spanish that questions the empirical adequacy and scope of previous analyses of clitic clusters in Romance. It is shown that the output of the Spurious se Rule is not identical to genuine se, at some level that is relevant for linearization of clitics within a cluster. A proposal is presented to capture the neglected data, and this is done in a way that illuminates the debate on the division of labour in clitic phenomena between phonology, morphology and syntax. Central questions in morphology, such as ordering of operations, syncretisms, linearization principles and consequences of lexical insertion are addressed and re-examined.